1988
DOI: 10.5694/j.1326-5377.1988.tb104473.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of plasma magnesium values in patients with acute myocardial infarction and patients with chest pain due to other causes

Abstract: Plasma magnesium concentrations were monitored daily in 86 patients who were admitted to a coronary care unit with a provisional diagnosis of acute myocardial infarction. Twenty‐six patients had suffered a myocardial infarction, while the remainder had angina or non‐cardiac chest pain. Magnesium levels were also obtained daily for five consecutive days in five normal subjects, who served as the control group. Calculations of the 95% confidence intervals on the differences between Day 1, Day 2 and individual su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A total of 17 out of the 31 studies included tumor depth invasion data, resulting in an invasion that included the submucosa in most cases [ 15 , 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 28 , 30 , 32 , 34 , 35 , 36 , 37 , 38 ]. A total of 26 out of the 31 papers reported dimensional data, and the median size was 16.5 mm (8–62.5 mm) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 26 , 28 , 31 , 32 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Six out of thirty-one authors reported a cut-off size of >10 mm for low tumor-related death [ 16 , 17 , 18 , 19 , 21 , 39 ], while 7 out of the 31 papers reported a larger cut-off size of >20 mm for an increased risk of gastric wall infiltration, metastasis at diagnosis, and relapse ( p < 0.001) [ 14 , 22 , ...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 17 out of the 31 studies included tumor depth invasion data, resulting in an invasion that included the submucosa in most cases [ 15 , 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 28 , 30 , 32 , 34 , 35 , 36 , 37 , 38 ]. A total of 26 out of the 31 papers reported dimensional data, and the median size was 16.5 mm (8–62.5 mm) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 26 , 28 , 31 , 32 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Six out of thirty-one authors reported a cut-off size of >10 mm for low tumor-related death [ 16 , 17 , 18 , 19 , 21 , 39 ], while 7 out of the 31 papers reported a larger cut-off size of >20 mm for an increased risk of gastric wall infiltration, metastasis at diagnosis, and relapse ( p < 0.001) [ 14 , 22 , ...…”
Section: Resultsmentioning
confidence: 99%